Democracy, Gender, and Social Policy in Russia A Wayward Society - Chandler, Andrea; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Through compelling and insightful analysis of the Russian case, this book explores the role that social welfare plays in regime transitions. It examines the role that gender and social welfare has played in Russia's post-communist political evolution from Yeltsin's assumption of the presidency to Putin's return for a third term as president in 2012.
Keywords: Political science; Public policy; Russia -- Politics and government; Human rights; Social policy; Sociology; Sex (Psychology).; Gender expression; Gender identity; Political Science and International Relations; Political Science; Public Policy; Social Policy; Gender Studies; Russian and Post-Soviet Politics; Human Rights